HUBUNGAN TINGKAT KEHADIRAN DAN PRESTASI BELAJAR PESERTA DIDIK PAKET C DI PKBM BUDI LUHUR SEMARANG - Jurnal Ekonomi (Journal of Economic Education and Entrepreneurship, 2026)
Attendance is considered one of the factors contributing to learners' academic achievement, including in non-formal education pathways such as Community Learning Activity Centers (PKBM). Preliminary data at PKBM Budi Luhur Semarang showed that 18.9% of Package C learners attended only during examinations, making attendance a relevant issue to examine. This study aims to determine (1) the attendance rate, (2) learning achievement, and (3) the relationship between attendance rate and learning achievement of Package C learners in the Economics subject at PKBM Budi Luhur Semarang. A quantitative descriptive approach was employed, involving the entire population of 74 Package C learners as the sample through total sampling (census). Data were collected through documentation of attendance records and odd-semester final examination scores, then analyzed using the Kolmogorov-Smirnov normality test and Pearson Product Moment correlation with SPSS assistance. The results showed that the attendance rate fell into the moderately high category (81.1%; 60 respondents), learning achievement was moderately high (86.5%; 64 respondents), and there was a strong positive relationship between attendance and learning achievement, with a correlation coefficient of r = 0.748 at a significance level of 0.000 (< 0.05). These findings indicate that higher learner attendance is associated with higher learning achievement, suggesting that attendance monitoring should be considered in learning evaluation within non-formal education institutions.